2005
DOI: 10.1002/adsc.200505193
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Haloalkylpyridines via Cp*RuCl‐Catalyzed Cycloaddition of 1,6‐Diynes with α‐Halonitriles. Unusual Halide Effect in Catalytic Cyclocotrimerization

Abstract: In the presence of 2 -5 mol % Cp*RuCl (cod), various 1,6-diynes reacted with a-monohaloand a,a-dihalonitriles at ambient temperature to afford 2-haloalkylpyridines in 42 -93% isolated yields. The failure of acetonitrile, N,N-dimethylaminoacetonitrile, phenylthioacetonitrile, and methyl cyanoacetate as nitrile substrate clearly showed that the a halogen substitution is essential for the present cycloaddition under mild conditions. The cycloaddition of unsymmetrical diynes bearing a substituent on one alkyne ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…17c Attempts to react (dimethylamino)acetonitrile with diyne 1b were unsuccessful, which may indicate that the inherent electronic structure of cyanamides, not a chelation effect, is the source of their high reactivity in this system. 21 To demonstrate the synthetic utility of this methodology, entry 1 was repeated on a 1 mmol scale leading to a comparable yield of 94 % (eq 5). …”
Section: Resultsmentioning
confidence: 99%
“…17c Attempts to react (dimethylamino)acetonitrile with diyne 1b were unsuccessful, which may indicate that the inherent electronic structure of cyanamides, not a chelation effect, is the source of their high reactivity in this system. 21 To demonstrate the synthetic utility of this methodology, entry 1 was repeated on a 1 mmol scale leading to a comparable yield of 94 % (eq 5). …”
Section: Resultsmentioning
confidence: 99%
“…Compared to other transition metals, Ru-based catalysts provide complementary access to pyridines with electron-decient nitriles, [80][81][82] which are oen challenging substrates for later transition metals like Co. 83 In contrast, cycloaddition using simple nitriles such as MeCN and PhCN is challenging with Ru due to oen endothermic nitrile insertion, 81 although examples of partially or fully intermolecular [2 + 2 + 2] cycloaddition with nitriles containing coordinating groups have been reported. 81,84,85 Detailed experimental and computational studies (both of [2 + 2 + 2] alkyne cyclotrimerization and pyridine formation) 22,86 have revealed that Cp*RuCl(COD)-catalyzed reactions of a,udiynes likely proceed rst through initial oxidative cyclization of the diyne to form ruthenacyclic biscarbenoid IM32. This intermediate, which related complexes have been structurally characterized via X-ray crystallography and NMR in several instances, 87 is shared between [2 + 2 + 2] pyridine formation, alkyne cyclotrimerization, and [2 + 2 + 1] pyrrole/furan/ thiophene synthesis (vide supra).…”
Section: Pyridinesmentioning
confidence: 99%
“…Notably, a number of the Ru-catalyzed [2+2+2] cycloaddition reactions for synthesis of pyridine were developed recently by Yamamoto and Itoh, 410,746 and Saá group. 747 In addition, Ni(0)-based catalytic systems for [2+2+2] synthesis of pyridines were recently reported.…”
Section: Synthesis Of Six-membered Aromatic Heterocyclesmentioning
confidence: 99%